2020
DOI: 10.1177/1049732320982276
|View full text |Cite
|
Sign up to set email alerts
|

“Love Can’t Be Taken to the Hospital. If It Were Possible, It Would Be Better”: Patients’ Experiences of Being Cared for in an Intensive Care Unit

Abstract: In this study, we aimed to explore the experiences of being cared for in an intensive care unit (ICU) through patients’ memories. We adopted a convergent parallel mixed-method design. We interviewed 100 patients shortly after their ICU discharge. Content analysis revealed 14 categories and 49 codes grouped according to themes corresponding to ICU Memory tool core components (factual events, feelings, delusions). The most critical patients reported mostly fragmented or delusional memories, the less critically-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The five themes derived from the data confirmed that the ICU experience was distressing and disorienting for the study's participants (Jackson et al, 2016). The ICU experience was depicted as an endless martyrdom (both physical and mental) where the imprisoned and suffering self was constantly exposed or threatened by the acts or omissions (real or imagined) of others (relatives or ICU staff) rendering the ICU a hostile environment (Sanson et al, 2021). Participants conveyed their lack of control and freedom, describing their positioning as a state of extreme vulnerability as they were entrapped and voiceless (Yang, 2016).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…The five themes derived from the data confirmed that the ICU experience was distressing and disorienting for the study's participants (Jackson et al, 2016). The ICU experience was depicted as an endless martyrdom (both physical and mental) where the imprisoned and suffering self was constantly exposed or threatened by the acts or omissions (real or imagined) of others (relatives or ICU staff) rendering the ICU a hostile environment (Sanson et al, 2021). Participants conveyed their lack of control and freedom, describing their positioning as a state of extreme vulnerability as they were entrapped and voiceless (Yang, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…Likewise, participants' descriptions linked the regain of consciousness in the ICU with optimism, control, and self-continuity. Sanson et al (2021) observed that the relief of being alive eventually follows the awakening process in most of the cases. Furthermore, consciousness entails the ability to communicate and the removal of tubes and medical devices; significant indicators of recovering control (Yang, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations